Perlindungan Hukum Bagi Korban Kelalaian Tindakan Medis: Studi Putusan Pengadilan Negeri Surabaya Nomor 840/Pid.B/2020/PN Sby tanggal 28 Januari 2021 - Santoso, Arif Dian; Rohmah Fani, Atifah; Fadhilatunnisa, Hilda; Ramadhan , Mahendra Utama Cahya (Medical : Jurnal Kesehatan dan Kedokteran, 2024)
Cases of medical negligence represent a critical issue in healthcare law, often causing significant harm to patients as victims. Such negligence not only leads to physical and psychological damages but also raises concerns about the adequacy of legal protections afforded to victims. This study aims to analyze the legal protections for victims of medical negligence by examining the decision of the Surabaya District Court, Case Number 840/Pid.B/2020/PN Sby, dated January 28, 2021. Employing a normative juridical method with a case-based approach, the research integrates document analysis and a review of relevant legal literature. The findings reveal that the court considered elements of negligence, legal consequences, and the fulfillment of victims' rights in its judgment. However, challenges persist in implementing comprehensive legal protections, particularly concerning compensation and victim rehabilitation. This article recommends strengthening regulations and healthcare policies to better safeguard victims’ rights while enhancing medical professionals’ understanding of legal obligations to prevent similar negligence in the future.